2022
DOI: 10.3389/fimmu.2022.930511
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus (LA-1) and butyrate inhibit osteoarthritis by controlling autophagy and inflammatory cell death of chondrocytes

Abstract: Osteoarthritis (OA) reduces the quality of life as a result of the pain caused by continuous joint destruction. Inactivated Lactobacillus (LA-1) ameliorated osteoarthritis and protected cartilage by modulating inflammation. In this study, we evaluated the mechanism by which live LA-1 ameliorated OA. To investigate the effect of live LA-1 on OA progression, we administered LA-1 into monosodium iodoacetate (MIA)-induced OA animals. The pain threshold, cartilage damage, and inflammation of the joint synovial memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Notably, the genus Lactobacillus has been widely proved to ameliorate OA and protect cartilage by modulating inflammation progression [ 64 ]. Keun Hyung Cho et al demonstrated that Lactobacillus supplement increased the level of Faecalibacterium that produces butyrate, thereby improving OA progression [ 29 ]. The InSug O Sullivan group also revealed that Lactobacillus treatment could effectively alleviate OA-related joint pain, protect against cartilage degradation, and reverse gut microbiota dysbiosis [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the genus Lactobacillus has been widely proved to ameliorate OA and protect cartilage by modulating inflammation progression [ 64 ]. Keun Hyung Cho et al demonstrated that Lactobacillus supplement increased the level of Faecalibacterium that produces butyrate, thereby improving OA progression [ 29 ]. The InSug O Sullivan group also revealed that Lactobacillus treatment could effectively alleviate OA-related joint pain, protect against cartilage degradation, and reverse gut microbiota dysbiosis [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the gut microbiota dominating in ACLT GNPs group such as Lactobacillus , Akkermansia , and Muribaculum were involved in the production of SCFAs [ 69 – 72 ]. In consideration of the key role of SCFAs in maintaining the homeostatic balance of intestine flora and the beneficial effects of SCFAs on alleviating OA progression, we investigated the alteration in the SCFAs concentration in fecal samples via a targeted metabolomics assay [ 29 , 73 ]. Consistent with the alteration in gut microbiota structure and composition, the PCA score plot and Orthogonal partial least-squares discriminant analysis (OPLS-DA) score plot demonstrated distinct clustering patterns, indicating a pronounced dissimilarity in the SCFA metabolism between the two groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin, an antioxidant used in the treatment of osteoarthritis, influenced rat metabolome and gut microbial composition by increasing Lactobacillus species and levels of SCFAs ( 125 ). The presence of Peptostreptococcaceae and Desulfovibrio , both of which hurt the intestine, and the absence of lactic acid-producing bacteria have been shown in rat models of osteoarthritis ( 126 ). Orally supplemented butyrate and Lactobacillus acidophillus (LA-1) ameliorated osteoarthritis in rats by downregulating inflammatory cytokines and improved autophagy by reducing necroptosis factors ( 126 ).…”
Section: Bioactives and Osteoarthritis: Metabolic And Anti-inflammato...mentioning
confidence: 99%
“…In contrast, ablation of SESN2 masked the benefits of exercise on gut microbiota ( Yu et al., 2023 ). Factors that influence the composition of the gut microbiota, such as exercise and aging, also influence the development of OA, and SESN2 has been implicated in all of these factors, perhaps as a central mediator linking the gut-bone axis ( O'Toole and Jeffery, 2015 ; Cho et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%